The Relationship between Tests of Neurocognition and Performance on a Laparoscopic Simulator. (12th June 2010) - Kuzbari, Oumar; Crystal, Howard; Bral, Pedram; Atiah, Rima A. A.; Kuzbari, Imad; Khachani, Amine; Aslam, Muhammad Faisal; Minkoff, Howard
Abstract : Objective . To estimate if there is a relationship between the results of tests of neurocognition and performance on a laparoscopic surgery simulator. Methods and Materials . Twenty participants with no prior laparoscopic experience had baseline cognitive tests administered (Trail Making Test, Part A and B (TMT-A and TMT-B), Grooved Peg Board Test, Symbol Digit Modalities Test, Symbol Digit Recall Test, and Stroop Interference Test), completed a demographic questionnaire, and then performed laparoscopy using a simulator. We correlated the results of cognitive tests with laparoscopic surgical performance. Results . One cognitive test sensitive to frontal lobe function, TMT-A, significantly correlated with laparoscopic surgical performance on the simulator (correlation coefficient of 0.534 withP < .05 ). However, the correlation between performance and other cognitive tests (TMT-B, Grooved Peg Board Test, Symbol Digit Modalities Test, Symbol Digit Recall Test, and Stroop Interference Test) was not statistically significant. Conclusion . Laparoscopic performance may be related to measures of frontal lobe function. Neurocognitive tests may predict motor skills abilities and performance on laparoscopic simulator.